2020
DOI: 10.1021/acsami.9b18264
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Nature of the Cu(I) Active Site in CuO/TiO2 for Excellent Low-Temperature CO Oxidation

Abstract: Stabilized Cu+ species have been widely considered as catalytic active sites in composite copper catalysts for catalytic reactions with industrial importance. However, few examples comprehensively explicated the origin of stabilized Cu+ in a low-cost and widely investigated CuO/TiO2 system. In this study, mass producible CuO/TiO2 catalysts with interface-stabilized Cu+ were prepared, which showed excellent low-temperature CO oxidation activity. A thorough characterization and theoretical calculations proved th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 61 publications
(87 reference statements)
4
40
0
Order By: Relevance
“…The concentration for the 5 mol% sample exhibited the sharpest changes at different temperatures. For bare TiO 2 NPs, no CO oxidation activity was observed below 500 °C, which is in good agreement with the literature [14]. For the CO oxidation profiles obtained using temperature-programmed reaction spectrometry, the sample heating rate was fixed at 20 K/min.…”
Section: Methodssupporting
confidence: 88%
See 1 more Smart Citation
“…The concentration for the 5 mol% sample exhibited the sharpest changes at different temperatures. For bare TiO 2 NPs, no CO oxidation activity was observed below 500 °C, which is in good agreement with the literature [14]. For the CO oxidation profiles obtained using temperature-programmed reaction spectrometry, the sample heating rate was fixed at 20 K/min.…”
Section: Methodssupporting
confidence: 88%
“…For thermal CO oxidation tests [7,14,15], Fang et al prepared CuO/TiO 2 catalysts using coprecipitation and impregnation methods and reported a CO oxidation onset at approximately 50 °C [14]. The high catalytic activity was attributed to the interfacial bond formation of hybrid Ti O Cu and the consequent stabilization of Cu + species.…”
Section: Introductionmentioning
confidence: 99%
“…The commonly used catalysts for CO oxidation are divided into noble metal catalysts such as Pt, 7,8 Au, 9–12 Pd, 13 Ag, 14 Ru, 15 Rh, 16 and Ir (ref. 17) and transition metal catalysts such as Cu, 18–21 Co, 22–25 and Mn. 26,27 In the reaction atmosphere (CO and O 2 ), the noble metal catalysts commonly show a higher CO catalytic activity than transition metal catalysts, whereas the drawback of high cost is a major limit for their wide applications.…”
Section: Introductionmentioning
confidence: 99%
“…Many techniques, such as morphology control [ 4 , 5 , 6 , 7 ], engineering defects [ 8 , 9 , 10 ], and construction of composite oxides [ 11 , 12 , 13 ] have been developed to improve the CO oxidation performance of transition metal oxide catalysts. Particularly, heterogeneous metal oxides that have exhibited excellent performances in CO oxidation fields [ 14 , 15 , 16 ] are the most widely studied because of their interactions of components [ 17 ]. Previous works have gradually demonstrated that heterogeneous metal oxides with synergistic interactions between two components are crucial for promoting catalytic performances [ 12 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%